Análise de itens de matemática do ENEM Digital via taxonomia de Bloom - Tamborlin, Julia Ribeiro (Universidade Federal de São Carlos, 2022)
The Revised Bloom Taxonomy (RBT) allows classifying the actions necessary for the examinee to obtain a satisfactory performance in solving items through their cognitive aspects. In the scenario of Computerized Tests, ENEM Digital is a test that applies 180 items in four areas of knowledge. From the analysis and classification of 45 digital items of Mathematics and its Technologies according to the RBT, the type of knowledge required by the examinee was defined to solve these items. Results show that the test is not well distributed in the two-dimensional table of the TBR and that there is a prevalence of items that require Effective Knowledge and items that require the skill "Apply".
ENEM Digital analysis of math items by Bloom's taxonomy
Keywords: Taxonomia de Bloom Revisada; Testes Educacionais; ENEM Digital; Revised Bloom's Taxonomy; Educational Tests; ENEM Digital; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL